Relationships between cardio-respiratory parameters and draught work output in F1 crossbred dairy cows under field conditions - Zerbini, E.; Gemeda, T.; O'Neill, D.H.; Howell, P.J.; Schroter, R.C. (Cambridge University Press, 1992)
Cardio-respiratory and mechanical work output variables were measured for four F1 crossbred dairy cows (average weight 475 kg) over a range of work levels. Resting (standing prior to exercise) heart rates (average 62 beats per min) and respiratory rates (average 21 breaths per min) were similar to those previously reported for cattle of similar weight. Minute ventilation was 0.146 1/min per kg. Resting oxygen uptake (average 0.0057 1/min per kg) was higher than values that have been reported for cattle under more relaxed conditions. The cows were exercised on an oval track by undertaking two bouts of activity for 500 m with a 5-min intervening recovery period. Walking increased minute ventilation by approximately 60 1/min and heart rate by 30 beats per min. Pulling a loaded sledge increased these variables further to approximately 200 1/min and 135 beats per min at 32 KJ/min (530 w), the highest work level studied. The calculated oxygen pulse was 72 ml per heart beat, with maximum oxygen consumption approximately 9 1/min. Overall working efficiency increased with work level to a maximum of approximately 26 percent at the highest work level. At this level the cows were pulling proportionately about 0.14 of their body weight. During periods of recovery after work the cardio-respiratory parameters varied as would be expected and recovery was usually complete within 7 min.